Observation of B0→D̄0K+K− and evidence for B0s→D̄0K+K− - Aaij, Roel; Adametz, Aleksandra; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Gersabeck, Evelina; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; et al. (Physical review letters, 2012)
The first observation of the decay B0→¯¯¯D0K+K− is reported from an analysis of 0.62 fb−1 of pp collision data collected with the LHCb detector. Its branching fraction is measured relative to that of the topologically similar decay B0→¯¯¯D0π+π− to be B(B0→¯¯¯D0K+K−)B(B0→¯¯¯D0π+π−)=0.056±0.011±0.007,where the first uncertainty is statistical and the second is systematic. The significance of the signal is 5.8σ. Evidence, with 3.8σ significance, for B0s→¯¯¯D0K+K− decays is also presented. The relative branching fraction is measured to be B(B0s→¯¯¯D0K+K−)B(B0→¯¯¯D0K+K−)=0.90±0.27±0.20. These channels are of interest to study the mechanisms behind hadronic B decays, and open new possibilities for CP violation analyses with larger data sets.